2006
DOI: 10.1111/j.1540-8175.2006.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma with Right Atrial Extension in a Young Patient with Congenitally Unguarded Tricuspid Orifice

Abstract: Hepatocellular carcinoma (HCC) with isolated right atrial metastasis is extremely rare; most cases are considered inoperable. We herein report the case of a 74-year-old man with HCC with isolated right atrial metas-tases without hepatic vein invasion; the right atrial lesion was resected because of the risk of heart failure and sudden death. Postoperatively, he underwent transcatheter arterial chemoembolization and radiofrequency ab-lation for intrahepatic HCC. He recovered completely, with a long-term surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Aside from the literature on FALD, there have been few reports, there have been few reports that liver tumors were associated with congenital heart disease [29,30,77]. In regard to FALD, the collected data from 6 studies showed that, 10 to 15 years after Fontan operation, hypervascular nodules were developed in approximately 20% to 30% of patients (Table 1) [17,68,[78][79][80][81].…”
Section: Liver Tumors Associated With Congenital Heart Diseasementioning
confidence: 99%
“…Aside from the literature on FALD, there have been few reports, there have been few reports that liver tumors were associated with congenital heart disease [29,30,77]. In regard to FALD, the collected data from 6 studies showed that, 10 to 15 years after Fontan operation, hypervascular nodules were developed in approximately 20% to 30% of patients (Table 1) [17,68,[78][79][80][81].…”
Section: Liver Tumors Associated With Congenital Heart Diseasementioning
confidence: 99%
“…As of 2006, only five cases of hepatocellular carcinoma had been reported in the setting of cardiac cirrhosis, including only one in a Fontan patient. 30,[51][52][53][54] In their autopsy study, Ghaferi and Hutchins described a patient who had died at the age of 24 years, 18 years after his Fontan surgery. At autopsy, a 4-cm liver mass with overlying hemorrhage was found protruding from the posteroinferior aspect of the left lobe.…”
Section: Prognosismentioning
confidence: 99%
“…Also concerning are case reports of hepatocellular carcinoma in patients with Fontan circulation and liver disease that are appearing with increasing frequency. As of 2006, only five cases of hepatocellular carcinoma had been reported in the setting of cardiac cirrhosis, including only one in a Fontan patient 30,51–54 . In their autopsy study, Ghaferi and Hutchins described a patient who had died at the age of 24 years, 18 years after his Fontan surgery.…”
Section: Prognosismentioning
confidence: 99%
“…[127][128][129][130][131] MR imaging with a hepatocyte-specific contrast agent has emerged as the preferred imaging modality for characterization of liver masses but may not be an option in the substantial subgroup of patients with CHD with pacemakers or defibrillators and may be limited in those with coils, vascular plugs, or other metallic devices. 132 Newer contrast-enhanced ultrasonography techniques recently have been approved for use in the United States and may increase the diagnostic accuracy of ultrasound for characterizing focal liver lesions.…”
Section: Managementmentioning
confidence: 99%